The effects of kettlebell mass and swing cadence on heart rate, blood lactate, and rating of perceived exertion during an interval training protocol - Wesley, C.; Kivi, D. (International Journal of Sports Science, 2017)
The purpose of this study was to determine the effects of kettlebell mass and swing cadence on heart rate, blood lactate, and rating of perceived exertion (RPE) during an interval kettlebell swing protocol in experienced female kettlebell users. Eighteen female participants completed three 5-minute rounds of a 15-second on, 15-second off interval kettlebell swing protocol using an 8, 12 and 16 kg kettlebell during three separate testing sessions. Each testing session used a cadence of 8, 10 or 12 swings per 15 second interval (SPI15). Mean values for heart rate, blood lactate, and RPE were measured for each 5-minute round of each testing session. The results of the repeated measures analysis of variance revealed no significant interaction effects were found between kettlebell mass and swing cadence for heart rate or RPE, but a significant interaction effect was found for blood lactate (F (4, 68) = 6.621, p < 0.001). Significant main effects were found for both kettlebell mass and swing cadence for heart rate (F (2, 34) = 97.302, p < 0.05), blood lactate (F (2, 34) = 33.273, p < 0.05), and RPE (F (2, 34) = 118.300, p < 0.05). The results revealed that the kettlebell swing, regardless of kettlebell mass or swing cadence, provided a level of intensity that was sufficient to increase aerobic capacity. The results suggest that various combinations of kettlebell masses and swing cadences can be utilized and implemented into a strength and conditioning program.